ChemInform Abstract: Microwave‐Assisted Synthesis of 3‐Substituted Indoles via Intramolecular Arene—Alkene Coupling of o‐Iodoanilino Enamines. Issue 52 (24th December 2013) - Lee, Won‐Il; Jung, Jong‐Wha; Sim, Jaehoon; An, Hongchan; Suh, Young‐Ger
Abstract A generally applicable and high‐yielding protocol for the synthesis of 3‐substituted indole derivatives is described.